2012
DOI: 10.1016/j.healthplace.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

After-school setting, physical activity, and sedentary behavior in 5th grade boys and girls

Abstract: After-school hours are considered critical for children’s physical activity (PA) and sedentary behaviors (SB); however, whether the after-school setting influences children’s activity patterns is unknown. This study examined the influence of after-school setting (i.e., parent report of the child’s usual after-school setting) on 5th grade children’s PA and SB, and differences by race/ethnicity. Boys whose parents reported they usually attended an after-school program had higher PA than boys who usually went hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
0
18
3
Order By: Relevance
“…Compared to the findings in the West (51, 52), more Chinese adolescents participated in adult-supervised after-school activity.…”
Section: Resultscontrasting
confidence: 67%
“…Compared to the findings in the West (51, 52), more Chinese adolescents participated in adult-supervised after-school activity.…”
Section: Resultscontrasting
confidence: 67%
“…All four studies were among children [ 21 , 26 , 29 , 31 ]. Of the remaining studies, 22 did not report where the children/adolescents were located after school [ 10 , 11 , 22 – 25 , 28 , 32 , 33 , 36 41 , 43 – 49 ] and five reported that the children/adolescents were at a variety of locations after school [ 27 , 30 , 34 , 35 , 42 ]. For synthesis of the results, these 27 studies were combined to represent children/adolescents at ‘unidentified locations’.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed TRACK protocol has been reported elsewhere (35). In brief, TRACK recruited children from 21 public elementary schools in two school districts in South Carolina.…”
Section: Methodsmentioning
confidence: 99%